Evaluating waters of Al-Jabbab River east of Wasit government for drinking and agricultural purposes - Abbass, Hamza; Abood, Abdullah (Al-Adab Journal, 2024)
This research is concerned with identifying the natural characteristics of the region and the climate factor and its impact on water resources and their seasonal and annual fluctuations. It is also interested in revealing the qualitative water characteristics of the Jabbab River and its suitability for various uses, including drinking and agriculture. Therefore, water samples were collected from the studied area in January 2023, and laboratory tests were conducted on them to determine their suitability for the aforementioned purposes. On the other hand, it is suitable for irrigation and for irrigating animals. This was clearly reflected in the different human uses of the land and the completed and unfinished projects.